Minimum efficiency for early selection of Dalbergia sissoo Roxb. progenies in semi-arid region of Central India - Rizvi, R.H.; Gupta, V.K.; Ahlawat, S.P.; ., Ajit; Datta, A. (Indian Journal of Agroforestry, 2020)
Nine years data of Dalbergia sissoo progeny trial established in semi-arid region of Central India was analysed. Age-age correlations were computed for tree traits viz. height, diameter at breast height and trait index ’D2H’; where H- height of tree in m, D- dbh in cm. It was found that age-age correlations were significantly high in case of D2H. A minimum age-age correlation model was employed for determining the selection efficiency for different proportion of population to be selected. Minimum selection efficiency for 10 percent population selection for three traits comes out to be 67.8, 69.4 and 70.8 percent, respectively. Selection of progenies at nine years of age must consist of seven trees out of ten trees for which height is more than 12.6 m or diameter at breast height is greater than 18.1 cm or D2H is more than 0.385 m3. On the basis of above criteria, ten trees of D. sissoowere selected for next tree improvement programme.